PELAKSANAAN PENILAIAN HASIL BELAJAR MENURUT IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN FISIKA KELAS X SMA DI KOTA PONTIANAK - Fatimah Fatimah; Stepanus Sahala; Haratua Tiur Maria S (Universitas Tanjungpura, 2019)
AbstractThis research have a purpose to review the suitability of authentic assessment implement by physic teachers with authentic assessment based on demand of curriculum 2013 suitable with the Permendikbud No. 66 Tahun 2013 that is attitude, knowledge, and skill assessment use the relevant instrument. The research’s method that used in this research is descriptive method. Sample in this research is SMA Negeri 7 Pontianak and SMA Negeri 8 Pontianak, choose with use the purposive sampling method. The instrument of data collector is student and teacher questionnaire, interview list for headmaster and teacher and also documentation that be related to authentic assessment. In the amount of 69,2 % of indicator in the plan of authentic assessment and 72,2 % of indicator in implementation of authentic assessment that implemented by physis teachers grade X Senior High School at Pontianak it has been happen well and suitable with demand of curriculum 2013 there are in Permendikbud No. 66 Tahun 2013. This research expected can used as reference in the implementing of authentic assessment in order to suitable with demand of curriculum 2013 based on Permendikbud No. 66 Tahun 2013. Keywords: Authentic Assessment, Curriculum 2013 and Physic Learning